Pelaksanaan Stimulasi Guru Terhadap Perkembangan Motorik Halus Anak Di Taman Kanak-Kanak Islam Nurul Falah Kota Payakumbuh - Septiani, Yohana; Yeni, Indra (Jurnal Family Education, 2022)
The purpose of this study was to find out the implementation of teacher stimulation on the development of children’s fine motor skills in the Nurul Falah Islamic Kindergarten in Payakumbuh City in the Even Semester of the 2021-2022 Academic Year. Childhood is the golden age for early childhood. At this age, all aspects of child development develop very rapidly. Various factors are involved in the development of a child’s fine motor skills. One of them is the teacher’s ability to design appropriate stimulation for children, so that it can encourage the development of children’s fine motor skills. This research uses a descriptive method with a qualitative approach, where the research results are not in the form of numbers but in the form of sentences. Observations and interviews, as well as documentation are used for the data collection process in this study. And also data analysis and interpretation techniques are carried out with steps such as collecting data, presenting data, and providing conclusions on the results obtained. The results of the study show that the Implementation of Teacher Stimulation of Children’s Fine Motor Development in Nurul Falah Islamic Kindergarten for the 2022/2023 academic year has been well implemented. In the planning carried out by the teacher in developing or designing parts of the learning materials (RPPM and RPPH) and adjusting them to existing indicators according to current conditions, using media, namely crayons and their devices, and children’s worksheets (LKA) money is made by the teacher to help so that the learning process can run well. In carrying out the teacher chooses several learning methods that can be used, namely demonstration methods, playing, hands-on practice and giving assignments and the form of assignments given is in the form of Children’s Worksheets (LKA) which are made by the teacher according to the children’s activities that week. In the evaluation carried out by the teacher, namely looking at and reviewing the extent to which the developmental achievements that have been passed by the child, and seeing the child’s learning outcomes.